Predicting bird diversity through acoustic indices within the Atlantic Forest biodiversity hotspot - Gaspar, Lucas P. [UNESP]; D. A. Scarpelli, Marina; Oliveira, Eliziane G.; Alves, Rafael Souza-Cruz [UNESP]; Gomes, Arthur Monteiro [UNESP]; Wolf, Rafaela [UNESP]; Ferneda, Rafaela Vitti [UNESP]; Kamazuka, Silvia Harumi [UNESP]; Gussoni, Carlos O. A. [UNESP]; Ribeiro, Milton Cezar [UNESP] (Frontiers, 2023)
The increasing conversion of natural areas for anthropic land use has been a major cause of habitat loss, destabilizing ecosystems and leading to a biodiversity crisis. Passive acoustic sensors open the possibility of remotely sensing fauna on large spatial and temporal scales, improving our understanding of the current state of biodiversity and the effects of human influences. Acoustic indices have been widely used and tested in recent years, with an aim towards understanding the relationship between indices and the acoustic activity of several taxa in different types of environments. However, studies have shown divergent relationships between acoustic indices and the vocal activity of most soniferous taxa. A combination of indices has, in turn, been reported as a promising tool for representing biodiversity in different contexts. We used uni- and bivariate models to test different combinations of 8 common indices in relation to bird assemblage metrics. We recorded twenty-two study sites in Brazil’s Atlantic Forest and three different types of environments in each site (forest, pasture, and swamp). Our results showed that 1) the best acoustic indices for explaining bird richness, abundance, and diversity were Bioacoustic and Acoustic Complexity; 2) the type of environment (forest, pasture, and swamp) influenced the performance of acoustic indices in explaining bird biodiversity, with the highest score model (biggest R2 value) being a combination between Acoustic Diversity and Bioacoustic indices. Our results do support the use of acoustic indices in monitoring the acoustic activity of birds, but combining indices is encouraged since it provided the best results. However, given the divergence we found across environments, we recommend that sets of indices are tested to determine which of them best describe the biodiversity pattern models for a specific habitat. Based on our results, we propose that biodiversity patterns can be predicted through acoustic patterns. However, the level of confidence will depend on the acoustic index used and on focal taxa of interest (i.e., birds, amphibians, insects, and mammals).
Keywords: acoustic remote sensing; acoustic surveys; Atlantic Forest; ecoacoustics; long-term ecological research; long-term monitoring; passive acoustic monitoring; tropical ecology